Operation of Brillouin fiber laser in the O-band region as compared to that in the C-band region - Ahmad, Harith; Norizan, Siti Fatimah; Zulkifli, Mohd Zamani; A. Ghani, Zawajer; Harun, Sulaiman Wadi (Institute of Physics Publishing, 2011)
A first time O band Brillouin fiber laser is demonstrated and compared with the C band Brillouin fiber laser. By utilizing a 20 km True wave fiber (TWF), the experiment demonstrated four Brillouin lines gen erated from the simple setup of Brillouin fiber laser. We compared the threshold between the Brillouin pump wavelength at 1310 nm which represent O band region and 1550 nm for C band region. It shows that the Bril louin threshold at O band region is smaller that C band. The channels spacing between these two bands are also different, where O band have 12.72 GHz spacing while 1550 nm have 10.25 GHz spacing.